2020
DOI: 10.1126/sciadv.aba1104
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity of K v 7.4 channels confers ultrafast electromechanical sensitivity and emergent properties in cochlear outer hair cells

Abstract: The mammalian cochlea relies on active electromotility of outer hair cells (OHCs) to resolve sound frequencies. OHCs use ionic channels and somatic electromotility to achieve the process. It is unclear, though, how the kinetics of voltage-gated ionic channels operate to overcome extrinsic viscous drag on OHCs at high frequency. Here, we report ultrafast electromechanical gating of clustered Kv7.4 in OHCs. Increases in kinetics and sensitivity resulting from cooperativity among clustered-Kv7.4 were revealed, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Power tuning curves in Fig. 3 D and E partially account for the OHC electrical corner frequency by driving the cell with a low-pass-filtered voltage, but no attempt was made to address the influence of MET kinetics ( 39 ), ion channel gating and expression ( 9 , 10 ), prestin expression ( 31 ), hair bundle electromotility ( 40 ), inhomogeneous expression and deformation, or mechanical forces associated with the traveling wave. The present OHC model is minimalistic, and reduces a complex cell with inhomogeneous expression and properties into a single lumped element, yet is sufficient to resolve the OHC speed paradox.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Power tuning curves in Fig. 3 D and E partially account for the OHC electrical corner frequency by driving the cell with a low-pass-filtered voltage, but no attempt was made to address the influence of MET kinetics ( 39 ), ion channel gating and expression ( 9 , 10 ), prestin expression ( 31 ), hair bundle electromotility ( 40 ), inhomogeneous expression and deformation, or mechanical forces associated with the traveling wave. The present OHC model is minimalistic, and reduces a complex cell with inhomogeneous expression and properties into a single lumped element, yet is sufficient to resolve the OHC speed paradox.…”
Section: Discussionmentioning
confidence: 99%
“…The RC corner is unusually high in OHCs owing to a standing K + conductance in the membrane ( 9 ). Ultrafast K + channel gating might also play a role in extending the effective RC ( 10 ). Evidence that OHCs can modulate voltage at auditory frequencies is compelling, but whether or not the motor mechanism can be driven by voltage cycle-by-cycle is less clear.…”
mentioning
confidence: 99%
“…Additionally, we previously modelled initial voltage influences on NLC as resulting from OHC molecular motor-motor (prestin) interactions 33 . For Kv 7.4 channels, cooperativity has been found to impart mechanical sensitivity to the channel in OHCs 61 . Another possibility is the presence of a conductive element influencing the interaction between voltage sensor charge and the membrane field, where that element alters with tension.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that besides voltage-dependence, outward K + channels such as Kv1.1/1.2 and Kv7 are modulated by mechanical stimuli (Hao et al, 2013;Perez-Flores et al, 2020), whereby the channel's voltage sensitivity is enhanced (Long et al, 2005). Kv1 and Kv7 channels are members of the cadre of outward K + channels that dominates the type I afferent AN membrane (Lv et al, 2010;Mo et al, 2002;Wang et al, 2013).…”
Section: Mechanical Sensitivity Of Auditory Neurons In Vitromentioning
confidence: 99%